Microbiological, electronic microscopy evaluation of the action of Decasan® and Horosten® on bacteria - V.V. Bobyr (Danylo Halytsky Lviv National Medical University, 2017)
Aim. The research was to study the action of Decasan® and Horosten® on ultra structure of Staphylococci and Salmonellas.